ANALISIS KEBIJAKAN DAN KOMUNIKASI PEMERINTAH DALAM MEMBUBARKAN FRONT PEMBELA ISLAM (FPI) - Pitoyo Ismail; Edy Prihantoro; Noviawan Rasyid Ohorella (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The news of the prohibition of the Government of the Republic of Indonesia against the Islamic Defenders Front (FPI) seized the public's attention. Several national media such as kompas.com, detik.com and republica.co.id have different points of view. Each media reported this phenomenon with different framing according to media ideology. The purpose of this research is to see the news framing of the news of the ban on the Government of the Republic of Indonesia against the Islamic Defenders Front (FPI) in the national online mass media. Methodologically this research uses a constructivism approach by applying textual analysis consisting of quantitative and qualitative analysis in the form of framing analysis. In addition, using intertextual analysis which includes analysis of text production and socio-cultural framing Robert Enmant. The results showed different frames on the 3 online portals. Kompas.com frames FPI news with a humanism frame, seeing the social impact of FPI's presence in society. The legal basis for the disbandment of FPI is clearly explained to show the truth to the public. Detik.com is almost the same as Kompas.com in framing the FPI phenomenon, by showing data and the fact that FPI has not yet received a permit again due to the organization's AD/ART problems. This is different from the Republika online frame which frames this reality in a straightforward manner, by showing evidence that FPI continues to fight injustice. The formation of negative opinions continues to be fought to provide a correct understanding of the community.